An implementation review of occlusion-based interaction in augmented reality environment - Shahidan, Mohamad Shahrul; Ibrahim, Nazrita; Mohamed Zabil, Mohd Hazli; Yusof, Azlan (2009)
Augmented Reality (AR) technology shows some potential in providing new approach of interaction with computer.It shares similar potential in Virtual Reality (VR) but at lower cost.In this paper, an AR application is developed to explore the capability of the interaction approach called Occlusion Based Interaction using low cost device.The implementation of the application is utilizing the ARToolKit library as the main library to handle the AR part while OpenGL and GLUT to handle the graphics manipulation and windows management respectively.